Interkoneksi Fikih Hisab Rukyat dan Ilmu Geodesi - Marwadi, Marwadi (Al-Manahij: Jurnal Kajian Hukum Islam, 2018)
Islamic studies, including fiqh, using an integration-interconnection approach with other sciences are important to do to get a more complete perspective. One of them is the interconnection of â€œhisab-rukyatâ€ fiqh with geodesy. In general, the study of the Qibla direction, the beginning of prayer times, the beginning of the qamariah month, and eclipses in â€œhisab-rukyatâ€ fiqh, uses the general formula of spherical trigonometry with a round earth reference. Round earth references in the study of the region differ from the real condition of the earth in the form of an ellipsoid as described in geodesy. To get more valid results, it is important to convert latitude and place height. The latitude of the place obtained by reference or GPS is the geodetic latitude with the earth reference in the form of an ellipsoid, whereas the spherical trigonometry formula refers to the shape of a round Earth. The place height obtained through GPS is the ellipsoid height, not the desired orthometric height (above the average surface of sea water). By converting these data, studies of the â€œhisab-rukyatâ€ fiqh can be more valid. By increasing the validity of the calculation results, the interconnection between â€œhisab-rukyatâ€ fiqh and geodesy appears in the form of complementation, meaning that data and findings of geodesy can complement data and analysis in â€œhisab-rukyatâ€ fiqh, so that it is possible to draw more valid conclusions.